Social Media Marketing: A Paradigm Shift in Business - Anjum, Arif; More, V. S.; Ghouri, Arsalan Mujahid (International Journal of Economics, Business and Management Studies, 2012)
This paper is produce to find the internet users preferences for social media marketing. For this purpose, Kierzkowski et al. (1996) study questionnaire’s three segments (attract, engage and retain) were adopted and made required changes according to find the customer’s response. The results shows that ‘mnemonic branding’, ’promotions’, ’piggyback advertising’ and ’adequate bandwidth’ are the best tools to attract customers. In engagement segment results interpretation, ‘lucky draws/contests’, ’informative and useful content’, ’transaction capabilities’, and’ creative programming’ are the preferred perceived tools by respondents. Retain segment analysis states that ‘security features’, ’dynamic content’, ’rapid information loading time’ and ’provide online order tracking’ in websites assist the business to retain their customers. Study revealed that businesses should invest more on online contents of websites, because fast pace living style enable customers to attach more to cyber world and they preferred to be the part of virtual globe.